Implementasi Metode Value Clarification Technique pada Pembelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar - Wulan Syarifatunnujum Isk; Erni Munastiwi (Mahesa Research Center, 2022)
This article aims to find out how to implement the Value Clarification Technique (VCT) learning method in Social Sciences (IPS) learning in elementary schools. The problem is focused on Social Science (IPS) subjects in elementary schools which have various types of material, the material must be delivered by conveying it in an appropriate method so that students understand what is being conveyed. Based on online observations in Wahyu and Nova's research which were analyzed qualitatively, the results showed that learning using audio-visual-assisted Value Clarification Technique (VCT) increased students' motivation in the learning process and learning outcomes. This study uses a meta-analysis method. Meta-analysis is quantitative because it uses numerical calculations and statistics for practical purposes. The instrument in this study used the Human Instrument. Data collection techniques will use documentation techniques. The data analysis technique used is quantitative data analysis with percentages and qualitative data analysis for data from narrative studies of studies found using SPSS 25, namely through the N-Gain Test and Paired Sample T-Test. Of the five journals collected, it turned out that implementing the Value Clarification Technique (VCT) learning method in Social Sciences (IPS) learning gave significant results, increasing from 0.2% to 71.76%.